2017
DOI: 10.2166/wst.2017.208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydraulic loading rate and aeration mode on nitrogen removal and nitrogen functional gene abundances in subsurface wastewater infiltration systems

Abstract: Matrix dissolved oxygen, nitrogen removal and nitrogen functional gene abundances in two artificial aeration modes, continuous aeration (CA) and intermittent aeration (IA), in subsurface wastewater infiltration systems (SWISs) under different hydraulic loading rates (HLRs) were investigated. Aeration not only successfully created aerobic conditions at 50 cm depth, but also did not change anoxic or anaerobic conditions at 80 and 110 cm depths. Meanwhile, aeration significantly enhanced chemical oxygen demand, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…() and Sun et al. () found that aeration was the most feasible method to ensure sufficient oxygen supply in SISs. The increase in HLRs resulted in decreased hydraulic retention time, and thus, NH4+‐N removal efficiency decreased for IAM and NAM SISs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…() and Sun et al. () found that aeration was the most feasible method to ensure sufficient oxygen supply in SISs. The increase in HLRs resulted in decreased hydraulic retention time, and thus, NH4+‐N removal efficiency decreased for IAM and NAM SISs.…”
Section: Resultsmentioning
confidence: 99%
“…Ye and Li (2009) reported greater rates of nitrification required DO concentrations above 1.5 mg/L. Jiang, Sun, Pan, Qi et al (2017) and Sun et al (2017) found that aeration was the most feasible method to ensure sufficient oxygen supply in SISs. The increase in HLRs resulted in decreased hydraulic retention time, and thus, NH + 4 -N removal efficiency decreased for IAM and NAM SISs.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Because nitrification is a two-step process, inorganic ammonium nitrogen is oxidized to nitrite nitrogen by a bacterial group that is commonly referred to as Nitrosomonas [12]. This group functions in anoxic-anaerobic environments and in the presence of facultative biomass [13][14].…”
Section: Introductionmentioning
confidence: 99%